Targets' Social Relationships as Antecedents and Consequences of Workplace Bullying: A Social Network Perspective - Pauksztat, Birgit; Salin, Denise (Frontiers in Psychology, 2020)
Research on workplace bullying has largely focused on individual and organizational factors that place individuals in a vulnerable position. Although theorists have highlighted social aspects of workplace bullying and its antecedents, the role of individuals’ social relations with other members of their organization has rarely been examined empirically. Drawing on insights from social network research and research on social rejection, the purpose of this study was to examine the relationship between exposure to bullying and employees’ informal social relationships (here: friendships; negative relationships) with other members of their organization. Data from two waves of surveys among 249 employees in eight organizations in Finland were analysed using stochastic actor-oriented modelling. We found that employees’ centrality (i.e., the number of their relationships) had no effect on exposure to bullying. However, exposure to bullying affected targets’ perceptions of their relationships with colleagues: employees who had experienced bullying subsequently reported significantly more friendship relationships, but not significantly more negative relationships, suggesting that aggressive or antisocial responses may be more muted in field settings than in experimental settings. Our study contributes to research on workplace bullying by providing a more detailed understanding of the relationship between workplace bullying and employees’ social relations, and by offering insights about the consequences of workplace bullying for targets’ social relations.